Approach to Stochastic Modeling of Power Systems - Rubtsov, Alexander (Electrical, Control and Communication Engineering, 2010)
This paper presents an approach to modeling power system that contains sources of stochastic disturbance. It is based on frequency analysis of linearized model of power system. Power system dynamic properties are accounted by equivalent transfer functions of machines and their control equipment. This will allow more accurate calculations for different analysis tasks. Methodology of system linearization is proposed and results of linearized model test are delivered.The research was made in frame of a project with funding participation of the European Commission.